Diz üstü amputelerde vücut imajı algısının ve proteze uyumun kognitif performansa etkisi - Gözaydınoğlu, Şüheda (Bezmialem Vakıf University, 2017)
The purpose of this study was to assess the effect of body image perception and compliance with the prosthesis on cognitive performance in transfemoral amputees, and to determine the factors that can lead to possible differences. Our research has been conducted the dates between December 2016- March 2017, at Bezmialem Vakıf University. Fourty transfemoral amputee, 30 males and 10 females, who had a traumatic amputation, with the average age 37,03±9,94 years were included in this study. Participants sociodemographic, amputation-specific and prosthetics usage related informations was recorded with the General Amputee Evaluation Survey which is prepared based on literature. Participants body image perception and compliance with the prosthesis paramaters were evaluated with ABIS (Amputee Body Image Scale) and TAPES (Trinity Amputation and Prosthesis Experience Scales). The assessment of the quality of life was done by NHP (Nottingham Health Profile). MoCA (The Montreal Cognitive Assessment) has been used to determine the cognitive ability of the participants. Neuropsycological subtests has been administered by dual task method during ambulation. For statistical analysis, a Windows-based SPSS 21 analysis program was used, significance level was accepted as p<0.05). The time passed after the amputation of the participants has been determined as 12,68±9,41 years. Individuals who are included in this study has an average 10,6±8,38 years of prosthetics usage. 45% of the participants regularly participate in sportive or physical activites, 55% of them do not participate any physical activity. Depending on the type of prosthesis, %50 of the participants are using microprocessor controlled and %50 are using hydraulic prosthetic knee. There was a statistically significant correlation between the ABIS, TAPES I. part subparamaters and cognitive performance (p<0,05). The relationship between the ABIS and TAPES I. part subparameters was statistically significant (p<0,05). Satisfaction with the body image and positive compliance to prosthesis was related improved quality of life. When the participants are divided into two groups based on their prosthetic type, it showed that ABIS, TAPES I. part subparameters and NSP, cognitive performance value difference have statistically significant (p<0,05). When the same data evaluated based on participants physical activity habits, regarding to cognitive peformance; any statistically significant difference was not found (p>0,05). Our study results shows that body image perception and compliance with the prosthesis may have effect on cognitive performance. By regulating body image perception and adding psychosocial adjustment to amputee rehabilitation programs, we believe that the amputee can improve its performance in cognitive functions such as attention, memory, and orientation, which are necessary for adaptation of the acquired injury, successful use of the prosthesis and independence on activities of daily living.
Çalışmamızda amaç; diz üstü amputelerde vücut imajı algısının ve proteze olan uyumun, kognitif performansı nasıl etkilediğini incelemek, olası farklılıklara sebep olabilecek faktörleri ortaya koymaktı. Çalışmamıza Aralık 2016-Mart 2017 tarihleri arasında Bezmialem Vakıf Üniversitesi'nde takip edilen, yaş ortalaması 37,03±9,94 yıl ve amputasyon nedeni travma olan 30 erkek, 10 kadın toplamda 40 diz üstü ampute dahil edildi. Olguların sosyodemografik, amputasyona özgü ve protez kullanımına ilişkin bilgileri literatürdeki değerlendirmelerden yola çıkarak hazırlanan Genel Ampute Değerlendirme Anketi ile kaydedildi. Olguların vücut imajı algısı ve proteze olan uyumu ABIS (Ampute Vücut İmajı Ölçeği) ve TAPES (Trinity Amputasyon ve Protez Deneyim Ölçeği) ile değerlendirildi. Yaşam kalitesinin değerlendirilmesi NSP (Nottingham Sağlık Profili) ile yapıldı. MoCA (Montreal Bilişsel Değerlendirme Ölçeği) olguların bilişsel yeteneğini değerlendirmek amacıyla kullanıldı. Nöropsikolojik alt testler ambulasyon sırasında olgulara çift görev verme yöntemi ile uygulandı. İstatistiksel analiz için Windows tabanlı SPSS21 (Statistical Package for the Social Sciences) analiz programı kullanıldı, anlamlılık düzeyi p<0,05 olarak alındı. Olguların amputasyon cerrahisini takiben geçen süre ortalama 12,68±9,41 yıl idi. Çalışmaya dahil edilen bireylerin ortalama 10,6±8,38 yıldır diz üstü protez kullandıkları görüldü. Olguların %45'inin düzenli spor alışkanlıkları olduğu, %55'inin spor veya fiziksel aktivitelere katılmadığı bulundu. Olgular kullanılan protezin türüne göre incelendiğinde %50'sinin mikroişlemcili, %50'sinin ise hidrolik diz üstü protez kullandığı görüldü. ABIS ve TAPES I. kısım alt parametreleri ile kognitif performans arasında istatistiksel olarak anlamlı ilişki bulundu (p<0,05). ABIS ile TAPES I. kısım alt parametreleri arasındaki ilişki istatistiksel olarak anlamlı idi (p<0,05). Vücut imajından duyulan memnuniyet ve proteze pozitif uyumun, yaşam kalitesini arttırdığı görüldü. Çalışmaya dahil edilen bireyler kullanılan protezin türüne göre 2 gruba ayrıldığında mikroişlemcili diz üstü protez kullananlar lehine ABIS, TAPES I. kısım, NSP ve kognitif performans değerleri arasındaki fark istatistiksel olarak anlamlı idi (p<0,05). Aynı değerlendirmeler bireylerin düzenli spor alışkanlıklarına göre incelendiğinde kognitif performans açısından düzenli spor yapanlarla yapmayanlar arasında anlamlı fark bulunmadı (p>0,05). Çalışmamızdan elde edilen sonuçlar amputelerde vücut imajı algısının ve proteze uyumun, kognitif performansı etkileyebileceğini göstermektedir. Vücut imajı algısının düzenlenmesi ve psikososyal uyumun ampute rehabilitasyon programlarına ilave edilmesiyle, amputenin edinilen özüre uyum sağlama, protezini başarılı bir şekilde kullanma ve günlük yaşam aktivitelerinde bağımsızlığın devamı için gerekli olan dikkat, bellek, oryantasyon gibi bilişsel fonksiyonlardaki performansını arttırabileceği görüşündeyiz.
Keywords: Fizyoterapi ve Rehabilitasyon = Physiotherapy and Rehabilitation; Ampütasyon = Amputation; Bacak = Leg; Beden imajı = Body image; Biliş = Cognition; Biliş bozuklukları = Cognition disorders; Hasta uyumu = Patient compliance; Protezler ve implantlar = Prostheses and implants